Complicações Associadas aos Enxertos Ósseos Aposicionais com Osso Autógeno - Florian, Fernanda [UNESP]; Conte Neto, Nicolau; Pereira Filho, Valfrido Antonio [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Vieira, Eduardo Hochuli [UNESP] (My University, 2010)
Introdution: Tooth extraction results in alveolar ridge resorption due to the progressive reabsorption, which frequently is a limitating factor of dental implants treatment, in function of the insufficient bone height for execution, could be indicated the use of grafts for increase of the alveolar edge. However, the success of the bone graft requests the meticulous attendance of the clinical stages. Proposition: The objective of this research was to evaluate the postoperative complications associated to the autogenous bone grafts. Materials and Methods: Through a random retrospective analysis, 90 file records of patients submitted to the surgical procedure of autogenous bone graft in the period of January from 2000 to the March of 2008. A clinical record was elaborated with base in the necessary data for this evaluation. Results: About the file data analysis, 59 female with average of 49,42 years and 31 male with average of 47,90 years. The previous diseases most related were arterial hypertension, stomachache and diabetis. The smokers was noticed in 13,3% of patients. The donor site most used was a mandibular ramus. The postoperative complications in receiving area represented 17,8% of file datas analysed and in the donor site only one patient showed parestesis. Conclusion: Among the total analyzed files it was observed that the postoperative complications associated with the autogenous bone grafts represented 18,9% of the patients submitted to the procedure, more frequently affecting the receiving area, obtaining partial exposure of the bone graft and absence of inserted gingiva on vestibular cortical bone.

Introdução: a exodontia dentária resulta em perda de osso alveolar, sendo este um fator limitante à possibilidade de reabilitação com implantes dentários, em função do volume ósseo insuficiente para sua execução, podendo ser indicado a utilização de enxertos visando ao aumento do rebordo alveolar. No entanto, o sucesso no emprego da enxertia óssea requer o acompanhamento minucioso das etapas clí- nicas. Proposição: o objetivo desta pesquisa foi o de avaliar as complicações pós-operatórias associadas aos enxertos ósseos autógenos aposicionais. Materiais e Métodos: Por meio de uma análise retrospectiva aleatória, foram avaliados 90 prontuários de pacientes submetidos ao procedimento cirúrgico de enxerto ósseo autógeno aposicional no período de janeiro de 2000 a março de 2008, através da elaboração de uma ficha clínica com dados necessários para essa avaliação. Resultados: dentre os prontuários analisados, 59 eram do gênero feminino, com média de 49,42 anos e 31 do gênero masculino com média de 47,90 anos. As doenças anteriores mais relatadas foram hipertensão, gastrite e diabetes. O tabagismo foi observado em 13,3% dos pacientes. A área doadora mais utilizada foi a linha oblíqua da mandíbula. As complicações pós-operatórias na área receptora representaram 17,8% dos prontuários analisados e, na área doadora, somente 1 paciente apresentou parestesia na região cirúrgica. Conclusão: dentre o total de prontuários analisados, observou-se que as complicações pós-operatórias associadas aos enxertos ósseos autógenos aposicionais representaram 18,9% dos pacientes submetidos ao procedimento, acometendo, mais frequentemente, a área receptora, tendo como resultado a exposição parcial do enxerto e ausência de gengiva inserida na cortical vestibular.
Complications related to inlay autogenous bone grafts
Keywords: Bone Transplantation; Postoperative Complications; Mouth Rehabilitation; Transplante Ósseo; Complicações Pós-operatórias; Reabilitação Bucal